2019
DOI: 10.1155/2019/2520179
|View full text |Cite
|
Sign up to set email alerts
|

Induced Ripening Agents and Their Effect on Fruit Quality of Banana

Abstract: Ripening is a genetically programmed highly coordinated irreversible phenomenon which includes many biochemical changes including tissue softening, pigment changes, aroma and flavour volatile production, reduction in astringency, and many others. Banana is one of mostly consumed fruit crops in the world. Since banana is a climactic fruit, induced ripening is essential in commercial scale banana cultivation and distribution to assure good flavour, texture, and uniform peel colour. Ethylene gas, acetylene gas li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 41 publications
6
70
1
8
Order By: Relevance
“…ey are often harvested at mature green preclimacteric stage and induced to ripen using arti cial ripening agents to obtain fruits with a same maturity stage and uniform peel colour [5]. e most popular method used in developed countries is exposing banana to ethylene gas in ripening rooms under controlled temperature and humidity [6]. Alternatively to ethylene gas, chemicals such as ethephon (2-chloroethylphosphonic acid) that can generate ethylene is widely used as a commercial ripening agent in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…ey are often harvested at mature green preclimacteric stage and induced to ripen using arti cial ripening agents to obtain fruits with a same maturity stage and uniform peel colour [5]. e most popular method used in developed countries is exposing banana to ethylene gas in ripening rooms under controlled temperature and humidity [6]. Alternatively to ethylene gas, chemicals such as ethephon (2-chloroethylphosphonic acid) that can generate ethylene is widely used as a commercial ripening agent in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…The results presented in Table 1 and Figure 1 showed that the unripe plantain has the lowest moisture content (50.66 ± 0.50 %). Reduction in moisture content may be majorly due to water loss through transpiration process, while some weight loss could be due to loss of carbon in respiration process ( Liu, 2003 ; Onwuka and Onwuka, 2005 ; Maduwanthi and Marapana, 2019 ). The plantain that was ripened using Potassium Dihydrogen Phosphate (PDP) has the highest moisture of 64.68 ± 0.10 %, while the naturally ripened plantain had a moisture content of 62.53 ± 0.20%.…”
Section: Resultsmentioning
confidence: 99%
“…The plantain that was ripened using Potassium Dihydrogen Phosphate (PDP) has the highest moisture of 64.68 ± 0.10 %, while the naturally ripened plantain had a moisture content of 62.53 ± 0.20%. The results obtained showed that the use of artificial ripening agent increased the moisture content in fruits thereby subjecting such food items to faster rate of microbial degradation and shorter shelf life, which can lead to quicker deterioration ( Adepoju and Adeniji, 2008 ; Maduwanthi and Marapana, 2019 ). Figure 1 showed the ash content ranging from 3.07 ± 0.10 % to 3.50 ± 0.00 % for CaC 2 and PDP respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Traditional Chinese Medicine (TCM) the extract of ripe fruit of S. grosvenorii has been variously reported to possess antidiabetic or antihyperglycaemic effects with potentials to improve insulin resistance [12,6]. Ripening of fruits is an irreversible process that usually affect the phytochemical and biochemical contents as well as organoleptic properties of fruits making them very edible and palatable [13]. Interestingly, the phytochemical reports have shown seasonal variations in the constituents of ripe and unripe fruit which might affect their medicinal properties.…”
Section: Discussionmentioning
confidence: 99%